THE EFFECT OF GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY (CSR), INVESTMENT DECISIONS, PROFITABILITY, AND INTEREST RATES ON STOCK PRICES IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Tasya Handayani; Husaini; Marzuki; Rico Nur Ilham (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to examine the Influence of Green Accounting (GA), Corporate Social Responsibility (CSR), Investment Decisions (PER), Profitability (ROE), and Interest Rates (SBI) on Stock Prices in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). Research data can be accessed on the official website www.idx.co.id. The sampling method used purposive sampling and obtained a sample of 17 companies for the 2019-2023 period. The data were analyzed using Panel Data Regression with the Eviews 12 application tool. The results of the study found that GA, CSR, PER and SBI did not have a significant effect. While ROE has a positive and significant effect on stock prices.